IMPROVING THE METHODOLOGY OF DEVELOPING STUDENTS’ WRITING SKILLS IN THE CONTEXT OF DIGITALIZATION - Ilhomhon ugli, Muydinov Mansurjon (Journal of Higher Education and Academic Advancement, 2025)
Objective: The proliferation of digital technologies has transformed educational practices globally, including the way writing skills are taught and developed in higher education. In Uzbekistan, higher education institutions are increasingly integrating digital tools into academic instruction, yet challenges persist in aligning these tools with effective pedagogy for writing development. Despite the global shift toward digital instruction, there is limited empirical evidence in the Uzbek context on the pedagogical effectiveness of digital tools for improving writing skills. This study investigates the impact of a digitally integrated methodology on students’ academic writing performance in higher education. Method: A mixed-methods experiment involving 60 undergraduate students from three universities revealed that the group exposed to digital tools (e.g., Google Docs, Grammarly, Padlet) showed statistically significant improvement in writing scores compared to a control group taught through traditional methods. Survey, interview, and observation data also indicated increased autonomy, engagement, and writing confidence in the experimental group. Result: The study offers a localized model of technology-enhanced writing instruction, incorporating collaborative platforms, AI-based feedback, and digital portfolios, tailored to the Uzbek educational context. Novelty: The findings underscore the importance of pedagogical planning, instructor training, and digital literacy support for students. Integrating digital tools into writing curricula, supported by reflective and collaborative strategies, can significantly improve learning outcomes and better prepare students for academic and professional communication in a digital era.